Kedudukan dan Harmonisasi Qanun Aceh Nomor 3 Tahun 2013 tentang Bendera dan Lambang Aceh dalam Sistem Hukum Nasional - Alfurqan Alfurqan (Yayasan Madinah Al-Aziziyah, 2026)
Aceh Qanun Number 3 of 2013 concerning the Aceh Flag and Emblem has not been implemented to date. This issue resurfaced when volunteers delivering humanitarian assistance to Aceh Tamiang on November 26, 2025, allegedly experienced repressive treatment for carrying the Aceh flag. This study aims to analyze the legal status of qanun within the Indonesian national legal system and examine the formal and substantive aspects of the enactment of Aceh Qanun Number 3 of 2013. This study employs a descriptive qualitative approach with a normative juridical research design conducted through library research. The primary legal materials include Law Number 11 of 2006, Law Number 12 of 2011, Government Regulation Number 77 of 2007, and Aceh Qanun Number 3 of 2013. Secondary legal materials consist of books and scholarly literature discussing legal system theory, legal principles, law-making theories, and the principles of proper legislative drafting. The findings indicate that qanun is legally equivalent to a regional regulation and occupies a position below statutes and government regulations within Indonesia’s hierarchy of laws and regulations. Based on the principle of lex superior derogat legi inferiori, Article 4 paragraph (1) of Aceh Qanun Number 3 of 2013 is considered inconsistent with the elucidation of Article 6 paragraph (4) of Government Regulation Number 77 of 2007. Therefore, judicial review should be considered while taking into account the sociopolitical background of Acehnese society underlying the formation of the qanun.